Dissecting how cancer cells regulate the alterntative splicing of RAC1B - Jordan, Peter (2022)
RAC1B is an alternative splicing variant of the small GTPase RAC1 and overexpressed in several tumor types. In colon cancer, RAC1B overexpression occurs in distinct genetic subtypes, in particular those carrying an oncogenic mutation in the BRAF gene [1]. RAC1B encodes a protein with additional 19 amino acids resulting from in-frame inclusion of alternative exon 3b, and adopts predominantly the GTP-bound active conformation in vivo. Its signaling activity favors cell cycle progression and cell survival through activation of the transcription factor NF-κB [2]. The splicing factor SRSF1 was identified as a key promoter of RAC1B splicing in colorectal cells and binds an exonic splice enhancer element in the alternative exon [3]. We found that RAC1B levels depended on two protein kinases, SRPK1 and GSK3β, which both act via the phosphorylation status of SRSF1 that determines its nuclear translocation and concomitant inclusion of exon 3b [4]. Recent evidence suggests that the described increase in RAC1B expression can be triggered in colorectal cells by pro-inflammatory signals from the tumor cell microenvironment. Together, our results demonstrate how signal transduction pathways can deregulate alternative splicing in tumor cells and that pharmacological intervention with the protein kinases involved may be of therapeutic value.